2020
DOI: 10.1111/jcpe.13396
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and severity of periodontal disease in Mainland China: Data from the Fourth National Oral Health Survey (2015–2016)

Abstract: AimTo evaluate periodontal conditions in adults in mainland China based on data from the 4th National Oral Health Survey.Materials and methodsData of adult subjects (35‐ to 44‐year‐old group [N = 4409], 55‐ to 64‐year‐old group [N = 4622], and 65‐ to 74‐year‐old group [N = 4428]) were analysed. Demographic, socio‐economic, personal habit, dental history, and health attitude data were obtained using a questionnaire. Periodontal condition was assessed using the standardized case definitions of the 2018 classific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
117
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(130 citation statements)
references
References 33 publications
5
117
0
1
Order By: Relevance
“…When the maximum PD value was added when determining complexity, the distribution of periodontitis stages changed dramatically (Table 3). Only a few epidemiological studies have used the new classification [12,[24][25][26][27][28]. However, the epidemiological surveys did not clearly explain how complexity was used to determine periodontitis staging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the maximum PD value was added when determining complexity, the distribution of periodontitis stages changed dramatically (Table 3). Only a few epidemiological studies have used the new classification [12,[24][25][26][27][28]. However, the epidemiological surveys did not clearly explain how complexity was used to determine periodontitis staging.…”
Section: Discussionmentioning
confidence: 99%
“…A rigorous analysis of evidence supposedly supporting the roles of various risk factors in terms of periodontitis prevalence and severity is very important when diagnosing and treating periodontal disease. The periodontitis prevalence varies among both developed and developing countries [8][9][10][11][12][13][14]. The historical lack of a standard periodontitis definition facilitating surveillance precludes any meaningful comparisons of findings in terms of variations in socioeconomic status, ethnicity or exposure to risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Periodontitis, a microbial‐related, multi‐factorial inflammatory disease that causes the loss of periodontal attachment, widely affects adults globally 1,2 . According to epidemiological investigations, the prevalence of periodontitis in adults of age 65–74 years in mainland China is 64.6%, with a 43.5% prevalence for severe periodontitis 3 . Evidence has suggested that periodontitis accelerates systemic diseases, such as respiratory tract infections, diabetes, cardiovascular disease, and cognitive impairment 4–6 …”
Section: Introductionmentioning
confidence: 99%
“…According to the 4th National Oral Health Epidemiology Survey conducted between 2015 and 2016 in China, the prevalence of dental caries is more than 90.0% for adults between the ages of 35 and 74 years old [1]. Furthermore, the prevalence of periodontitis among middleaged adults ranging from 35 to 44 years old is 52.8% [2]. Such oral health diseases and problems are associated with a lack of dental services utilization [3][4][5].…”
Section: Introductionmentioning
confidence: 99%